Teaching Recount Writing Skill Based on Moral Value - Nusriani Basir; Arqam Madjid; Magdahalena Tjalla; Abd. Haris Sunubi; Zulfa Zulfa (Universitas Muhammadiyah Enrekang, 2023)
Moral values are defined as guidelines that assist a person in deciding between right and wrong. In order to create honest, credible, and fair judgments and relationships in daily life. This study aims to analyze how to improve the recount writing skill students of SMP Negeri 7 Alla and explore the way of teaching recount writing skill based on the moral values of Domestic Enrekang culture at SMP Negeri 7 Alla. This research was conducted teaching recount writing skill to the eighth grade student of SMP Negeri 7 Alla. This type of research is a Classroom Action Research (CAR) and the data is collected by test and observation. The researcher implementation procedure of CAR started with situation analysis, action planning, action implementation, reflection, and evaluation of the impact of the action. The finding showed that the mean score every cycle has increased. In pre-cycle, the students gain mean score 56.6. it showed that the ability of students in writing recount was poor. In the cycle I, the student gain mean score 65.5. it showed that there was progress of student ability in cycle I. In cycle II, the student got mean score 73.2. It showed that Cycle II greater that Pre-cycle and cycle I. it also prove that students have high progress in recount writing. Keywords: moral value, teaching, recount text, writing.